Lives on the Line: Clinical Presentations and Outcomes of Pediatric Trauma in an Emergency Department in Pakistan - Iffat, Aisha; Mukhtar, Sama; Munawar, Sadaf; Rashid, Muhammad; Saleem, Maryam (Biological and Clinical Sciences Research Journal, 2025)
Pediatric trauma remains a significant public health concern worldwide and is a leading cause of morbidity and mortality. Understanding pediatric trauma patients' clinical presentation and outcomes is crucial for optimizing clinical care, guiding targeted prevention strategies, and streamlining resource allocation in High-volume, low-resource setups. Objective: To determine pediatric patients' clinical presentation and outcomes in the Emergency Department of The Indus Hospital and Health Network Korangi, Karachi. Methodology: This Cross-sectional study was conducted at the Pediatric Emergency Department, The Indus Hospital and Health Network, Karachi, from July 2024 to December 2024. Data was collected for age, gender, vital signs at ED arrival (mechanism of injury, time lapse before ED presentation, injury severity score (ISS) at ED arrival, and outcomes Results: Data from 90 patients were analyzed. The mean age was 8.2 ± 3.1 years, with a male predominance (60%). Falls (40%) and road traffic accidents (35%) were the most common mechanisms of injury. The mean ISS was 8.5 ± 3.7, with severe injuries (ISS > 15) observed in 20% of cases. Most Delayed ED presentation(4.1 +/- -- min) was documented in cases of road traffic accidents. We reported a mortality of 10%, primarily associated with severe injuries and RTAs. Conclusion: Falls and RTAs are the most frequent mode of injury in children ≤ 14 years of age and pose a significant burden on Emergency Departments. Delayed presentation to the ED due to a lack of prehospital care and severe injuries is associated with poor outcomes. Preventive measures, improved prehospital care, and enhanced hospital preparedness are mandated to reduce the burden of morbidity and mortality.